Bridging Epistemology and Practice: A Model for the Integration of Philosophy of Science in the Governance of Madarasah - Rodiyah, Sinta; Sari, Ria Puspita; Koderi, Koderi; Fakhri, Jamal (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This article discusses the urgency of developing an integrative model that connects epistemological aspects and managerial practices in the governance of madrassas and pesantren in response to the challenges of contemporary Islamic education. This research uses a qualitative approach with a literature study method through the analysis of books, scientific journals, and Islamic education policy documents. The analysis was carried out in a descriptive-analytical manner to find the relationship between the epistemological dimension and managerial practice. The results show that the integration of three approaches to Islamic epistemology bayani (textual), irfani (spiritual), and burhani (rational) strengthens the conceptual foundations of Islamic education governance. Managerial practices show efforts to adapt to the national curriculum, use of digital technology, and leadership capacity building, although still facing limited resources. The synthesis of these two aspects results in a scientific and contextual model of governance, which balances the values of tradition with the demands of modernizing Islamic education.